Assessing national vulnerability to phosphorus scarcity to build food system resilience: The case of India. (15th June 2019) - Nanda, Madhuri; Cordell, Dana; Kansal, Arun
Abstract: The scarcity of phosphorus worldwide led researchers to develop indicators of national vulnerability to phosphorus scarcity, however this has not been applied at a national level so far. A systematic approach is described here to identify country-specific indicators of such vulnerability, in this case for India, based on literature and stakeholder engagement. The indicators are then aggregated to compute a phosphorus vulnerability index (PVI) to help policymakers formulate strategies towards building national resilience towards scarcity of phosphorus. For India, the key indicators include import dependence, soil fertility, purchasing power of farmers, and their access to credit. A PVI of 37.29 puts India in the 'highly vulnerable' category. Existing schemes targeted for agricultural sector in India are assessed for their ability to manage phosphorus vulnerability and for building resilience. Other developing countries with similar challenges can easily replicate the approach. Graphical abstract: Image 1 Highlights: National Phosphorus vulnerability has linkages with both global and local factors. P Vulnerability Index (PVI) is a valuable tool strategizing local actions for P security. Co-benefits of existing agricultural schemes have limited impact in improving PVI for India. India can shift from highly vulnerable to a P-resilient nation with P-targeted policies.